You are on page 1of 6

CHAPTER 43 THE RELATIONSHIP BETWEEN

TRIGONOMETRIC AND HYPERBOLIC FUNCTIONS

EXERCISE 180 Page 483

1. Verify the following identities by expressing in exponential form:

sinh A cosh B + cosh A j sinh B

L.H.S. = sin j(A + B) = j sinh(A + B)

R.H.S. = sin jA cos jB + cos jA sin jB

= j sinh A cosh B + cosh A j sinh B

= j(sinh A cosh B + cosh A j sinh B)

= j sinh(A + B) from Table 24.1, page 218

Hence, L.H.S. = R.H.S. i.e. sinh A cosh B + cosh A j sinh B

2. Verify the following identities by expressing in exponential form:

cos j(A – B) = cos jA cos jB – sin jA sin jB

L.H.S. = cos j(A – B) = ch(A – B) from (5), page 483

R.H.S. = cos jA cos jB + sin jA sin jB

= ch A ch B + j sh A j sh B from (5) and (6), page 483

= ch A ch B + j 2 sh A sh B

= ch A ch B – sh A sh B

= ch(A – B)

Hence, L.H.S. = R.H.S. i.e. cos j(A – B) = cos jA cos jB + sin jA sin jB

3. Verify the following identities by expressing in exponential form: cos j2A = 1 – 2 sin2 jA

L.H.S. = cos j2A = ch 2A from (5), page 483

723 © 2014, John Bird

= 2 cos j   sin j   = 2 ch   j sh    2   2   2   2   A+ B   A− B  = 2 j ch   sh    2   2   A B A B A B A B = 2 j ch ch + sh sh  sh ch − ch sh   2 2 2 2 2 2 2 2 724 © 2014. sin jA cos jB = [sin j(A + B) + sin j(A – B)] 2 5. i.H. L.S.R.S. = 1 – 2 sin 2 jA = 1 – 2(sin jA)(sin jA) = 1 – 2(j sh A)(j sh A) = 1 – 2 j 2 sh 2 A = 1 + 2 sh 2 A = ch 2A from Table 24.H.H.H. = sin jA cos jB = j sinh A cosh B 1 R.S.1.H.H.e.H.H. = R. cos j2A = 1 – 2 sin 2 jA 4. Verify the following identities by expressing in exponential form:  A+ B   A− B  sin jA – sin jB = 2 cos j   sin j    2   2  L.S. = sin jA – sin jB = j sh A – j sh B = j(sh A – sh B)  A+ B   A− B   A+ B   A− B  R. John Bird .S. L. Verify the following identities by expressing in exponential form: 1 sin jA cos jB = [sin j(A + B) + sin j(A – B)] 2 L.e. 2 page 218 1 = [j (2 sinhA cosh B)] 2 = j(sinh A cosh B) 1 Hence. = R.S.S.S. = [sin j(A + B) + sin j(A – B)] 2 1 = [j sinh(A + B) + j sinh(A – B)] 2 1 = [j (sinhA cosh B+ cosh A sinh B) + j (sinhA cosh B – cosh A sinh B)] from Table 24. i.S.H.1. page 218 Hence.

1.H. page 218  2  2  = j [ sh A – sh B ] = L.  A B A B A B A B A B A B  ch 2 ch 2 sh 2 ch 2 − ch 2 ch 2 ch 2 sh 2 + sh 2 sh 2 sh 2 ch 2  = 2j   A B A B − sh sh ch sh  2 2 2 2   A A B A B B A B B B A A = 2 j ch sh ch 2 − ch 2 ch sh + sh 2 sh ch − sh 2 sh ch   2 2 2 2 2 2 2 2 2 2 2 2  A A B B B B A A  = 2 j sh ch  ch 2 − sh 2  + sh ch  sh 2 − ch 2    2 2 2 2 2 2 2 2   A A B B B B A A  = 2 j sh ch  ch 2 − sh 2  − sh ch  ch 2 − sh 2    2 2 2 2 2 2 2 2   A A B B  = 2 j sh ch (1) − sh ch (1)  from Table 24. John Bird .S 725 © 2014. page 218  2 2 2 2   A A B B = j  2sh ch − 2sh ch   2 2 2 2   A  B  = j sh 2   − sh 2    from Table 24.1.

e.e. cosh (θ + φ) = cosh θ cosh φ – j 2 sinh θ sinh φ i. =    cos jθ  2  1  i. Use the substitution A = jθ (and B = jφ) to obtain the hyperbolic identities corresponding to: sin(A – B) = sin A cos B – cos A sin B Substituting A = jθ and B = jφ in sin(A – B) = sin A cos B – cos A sin B gives: sin(jθ – jφ) = sin jθ cos jφ – cos jθ sin jφ i. 2  1  1 + ( j tanh θ ) 2 i. cosh (θ + φ) = cosh θ cosh φ + sinh θ sinh φ since j 2 = –1 3.e. Use the substitution A = jθ (and B = jφ) to obtain the hyperbolic identities corresponding to: 1 + tan2A = sec2A Let A = jθ then 1 + tan 2 A = sec 2 A becomes: 1 + tan 2 ( jθ ) = sec 2 ( jθ ) 1 + ( tan jθ ) = ( sec jθ ) 2 2 i. j sinh (θ – φ) = j sinh θ cosh φ – j cosh θ sinh φ 726 © 2014. Use the substitution A = jθ (and B = jφ) to obtain the hyperbolic identities corresponding to: cos(A + B) = cos A cos B – sin A sin B Let A = jθ and B = jφ then cos(A + B) = cos A cos B – sin A sin B becomes: cos(jθ + jφ) = cos jθ cos jφ – sin jθ sin jφ i.e. 1 − tanh 2 θ = sech 2 θ 2.e.e. John Bird .EXERCISE 181 Page 485 1. 1 + j tanh θ = 2 2    ch θ  i.e. cos j(θ + φ) = cosh θ cosh φ – j sinh θ j sinh φ from (5) and (6) on page 483 i.e.

sinh (θ – φ) = sinh θ cosh φ – cosh θ sinh φ 4. j cosh θ sinh φ = j [sinh (θ + φ) – sinh (θ – φ)] 2 1 i.e. j cosh θ sinh φ = [ j sinh (θ + φ) – j sinh (θ – φ)] 2 1 i. j tanh 2θ = = 1 − ( j tanh θ ) 1 − j 2 tanh 2 θ 2 2 j tanh θ i.e.e.e.e. cosh θ sinh φ = [sinh (θ + φ) – sinh (θ – φ)] 2 727 © 2014. j sinh (θ – φ) = j (sinh θ cosh φ – cosh θ sinh φ) i.e.e. Use the substitution A = jθ (and B = jφ) to obtain the hyperbolic identities corresponding to: 2 tan A tan 2A = 1 − tan 2 A 2 tan A Substituting A = jθ in tan 2 A = 1 − tan 2 A 2 tan jθ gives: tan 2 jθ = 1 − tan 2 jθ 2 j tanh θ 2 j tanh θ i.e.e. j tanh 2θ = 1 + tanh 2 θ 2 tanh θ i. John Bird . tanh 2θ = 1 + tanh 2 θ 5.i. cosh θ j sinh φ = [sin j(θ + φ) – sin j(θ – φ)] 2 1 i. Use the substitution A = jθ (and B = jφ) to obtain the hyperbolic identities corresponding to: 1 cos A sin B = [sin(A + B) – sin(A – B)] 2 1 Let A = jθ and B = jφ then cos A sin B = [sin(A + B) – sin(A – B)] 2 1 becomes: cos jθ sin jφ = [sin(jθ + jφ) – sin(jθ – jφ)] 2 1 i.

− ( sin h3θ ) = sin h θ − sin h 3θ 4 4 1 3 i.e.e.e.  2 − 1 = 1 ( jthθ )  ch θ  2 1 and ( sech 2θ − 1) = 1 j 2th 2θ i.  − 1 = 1 tan 2 jθ  cos 2 jθ  1  1  i. Use the substitution A = jθ (and B = jφ) to obtain the hyperbolic identities corresponding to: 3 1 sin3 A = sin A – sin 3A 4 4 3 1 Substituting A = jθ in = sin 3 A sin A − sin 3 A 4 4 3 jθ 3 1 gives: = sin sin jθ − sin 3 jθ 4 4 3 1 i. sin h3θ = sin h 3θ − sin h θ 4 4 7. − coth 2 θ ( sech 2 θ − 1) = 1 or coth 2 θ (1 − sech 2 θ ) = 1 728 © 2014. Use the substitution A = jθ (and B = jφ) to obtain the hyperbolic identities corresponding to: cot2 A(sec2 A – 1) = 1 Substituting A = jθ in cot 2 A ( sec 2 A − 1) = 1 gives: cot 2 jθ ( sec 2 jθ − 1) = 1 1  1  i.  − 1 =1 ( tan jθ )  ( cos jθ )  2 2 1  1  i. ( sin h3θ ) j 3= j sin h θ − j sin h 3θ 4 4 3 1 Dividing by j gives: j 2 ( sin = h3θ ) sin h θ − sin h 3θ 4 4 3 1 i.6.e. John Bird .e.e.e.